PATH-47. THE CHALLENGE AND THERAPEUTIC RELEVANCE OF A NON-MATCHING CLASSIFIER OUTPUT USING GENOME-WIDE DNA METHYLATION FOR CLINICAL ROUTINE. (14th November 2022) - Drexler, Richard; Eckhardt, Alicia; Bode, Helena; Fita, Krystian; Lamszus, Katrin; Westphal, Manfred; Dührsen, Lasse; Schüller, Ulrich; Mohme, Malte
Abstract: DNA methylation-based classification of central nervous system tumours has been increasing in importance for routine clinical workups and offers novel opportunities in discriminating subtypes which could lead to a more customized therapy. However, there are still unclassifiable entities for which defining an effective therapeutic regimen is challenging. The aim of our study was to gain further insight in these challenging cases. We included 81 patients with a calibrated score below 0.9 in the classifier output, who underwent surgery for a tumour of the central nervous system (CNS). 47 patients had a different output using the classifier version v11b4 when compared to their histological diagnosis. Of these, 41 patients (87.2 %) did not have any diagnosis from the methylation classifier ("no matching methylation class"). Surgical and clinicopathological features as well as DNA input had no impact on the calibrated score. Cases with non-classifiable tumors had a significantly longer time until a decision for adjuvant therapy and these cases were presented more often in neurooncological tumor boards (p< 0.01). Further analyses in 23 glioblastoma patients revealed comparable results for the overall survival, but a significantly shorter progression-free survival in cases with a discrepancy between the histological and classifier diagnosis. Application of the latest classifier version v12.5 enabled classification in 67.9% of cases, resulting in re-classification with a high calibrated score (> 0.9) in 25.7% of the tumors. Taken together, our study presents unclassifiable cases and the possible clinical impact when waiting for the accurate diagnosis in these challenging cases. Even though DNA methylation profiling significantly contributes to advanced CNS tumour diagnostics, clinicians should be aware of a prolonged interval to treatment initiation, especially for highly malignant brain tumours. Therefore, we would recommend to schedule adjuvant treatment as early as possible if surgical and histological results are suspicious for this disease.